Null positioning of dipole antenna array considering coupling effect - Abdul Malek, Norun; Mat Ramli, Nurwahida; Abdullah, Khaizuran (Praise Worthy Prize, 2017)
Antenna array is a set of antennas that are arranged together with different excitations (amplitude and phase) and used in beamforming techniques. The difference in phases are combined together to make the array acting like a single antenna with better steering capability over a single antenna. However, the receiving antenna arrays are influenced by intentional or unintentional interference. In this research, a null positioning technique has been introduced to the antenna array to efficiently mitigate the interference. An efficient method utilizing Genetic Algorithm (GA) is used to position the nulls in the direction of interference of circular array dipole antennas. In forming the null, GA randomly searches the best fitness function to position the null to any direction. Then, the effect of mutual coupling between the antenna elements is also considered in this research. As a result, the accuracy of radiation pattern of antenna array will be increased. It is observed that the mutual coupling decreases when the spacing between element increases. The simulation results show that nulls can be steered successfully using GA with and without mutual coupling effect. The mutual coupling effect has been taken into account and need to be considered especially in a closely spaced antenna arrays.